A Japanese study to assess immunogenicity and safety of a typhoid Vi polysaccharide vaccine. Issue 48 (27th November 2015) - Miyazu, Mitsunobu; Kikuchi, Hitoshi; Hamada, Atsuo; Fukushima, Shinji; Ouchi, Kazunobu; Bosch Castells, Valerie; Mihara, Hanako; Bonnet, Marie-Claude
Highlights: Although rare in Japan, imported cases of typhoid fever can occur in travelers. Safety and immunogenicity of a typhoid vaccine were assessed in a Japanese population. The typhoid Vi polysaccharide vaccine, Typhim Vi ®, was well tolerated and immunogenic. Abstract: Background: Although typhoid fever is rare in Japan, imported cases have been reported occasionally in travelers returning from endemic areas. To achieve licensing of a typhoid Vi polysaccharide vaccine (Typhim Vi ® ) and make it widely available in Japan, this study was conducted at the request of the Japanese Ministry of Health Labor and Welfare to assess the immunogenicity and safety of this vaccine when given as a single dose (the recommended schedule of administration) in a Japanese population. Methods: In this multi-center, open-label, non-comparative, intervention study performed in Japan, 200 healthy volunteers (188 adults [≥18 years of age], 7 adolescents [12–17 years of age] and 5 children [2–11 years of age]) were administered Typhim Vi ® . Immunogenicity was assessed 28 days after vaccinations using an ELISA method of anti-Vi antibody detection. A 4-fold increase in anti-Vi titer was considered as the threshold for seroconversion for anti-Vi antibodies. Safety was assessed up to 28 days following vaccination. Results: Overall, 92.0% (95% confidence interval [CI]: 87.3–95.4%) of participants achieved seroconversion 28 days after a single dose of typhoid Vi polysaccharide vaccine. GMTs of Vi antibody titers increased from 6.6 (95% CI: 5.8–7.4) prior to vaccination to 157.3 (95% CI: 135.1–183.2) on Day 28 after vaccination. The geometric mean of individual anti-Vi antibody titer ratios (Day 28/Day 0) was 23.9 (95% CI: 20.3–28.3). There were no immediate adverse events and no adverse events led to the discontinuation of participants from the study. Across all age groups, pain and myalgia were the most frequently reported injection site and systemic reactions, respectively. Most of these reactions were mild in intensity and resolved within 7 days. Conclusions: A single dose of typhoid Vi polysaccharide vaccine, Typhim Vi ®, demonstrated good safety and immunogenicity profile in a Japanese population.